DESIGNING ENGLISH LANGUAGE TESTING USING A WEB-BASED MONITORING PLATFORM - Widia Resdiana; Dewi Selviani Yulientinah (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
As the learning activities were switched to online because of the COVID-19 pandemic, changes in the way of learning also affects the facilities used both in the learning and the test activities. This situation requires language test developers to think more creatively to make the test online and to provide safe environment for the test without compromising the validity of the test. This paper aims to describe the steps of choosing the appropriate application used for the online language test, trials of the test, and the user manual made for the test. So, it requires new guidelines and new way of proctoring the online language tests. There are 4 steps that accommodate the needs, 1) Technology Selections, 2) User Manual Making, 3) Trials, and 4) Question Making. The process of designing a language assessment following the steps sends a platform suitable for the needs. Because of the restrictions from the COVID-19 , the platform can provide a valid and safe environment for the language testing because it was conducted based on web monitoring. Then, the platform can provide webcam monitoring and variations of questions in language assessment, such as audio for listening tests. User Manuals help the test taker in understanding on how to access the platform, and the trials made it more comprehensive. From the questionnaiers, it can be concluded that the platform help to solve the problems and the test can be conducted without problematic issues.